Nishkāma samājasevī Śrī Rāvatamala Pārakha : abhinandana grantha - Pārakha, Rāvatamala, 1909-; Agravāla, Subodhakumāra (Loka Saṃskrti Śodha Saṃsthāna, 1982)
Festschrift honoring Rāvatamala Pārakha, b. 1909, social activist from Rajasthan now living in Calcutta; comprises articles on his life and work.